(untitled) (TERRA LATINOAMERICANA, 2026)
The search for non-microbial biostimulants to optimize sustainable hydroponic production is a rapidly expanding research area; however, the synergistic ef fect between protein hydrolysates and silicon (Si) in horticultural crops has not yet been fully elucidated. This study evaluated the biostimulant ef fect of the combined application of three protein hydrolysates (animal, plant, and mixed-origin) and three Si concentrations (10, 15, and 20 mg L-1) on growth, yield, and net CO₂ assimilation rate of grape tomato plants (Solanum lycopersicum L.) grown in a hydroponic system, as well as on the chemical characteristics of the substrate and leachate. A randomized complete block design with a 3 × 3 factorial arrangement was used, with four replications. Results showed that the plant-derived hydrolysate exhibited the greatest biostimulant potential by increasing biomass production, fruit size, weight, yield, and net photosynthetic rate, while reducing total soluble solids. Si increased net CO₂ assimilation at 20 mg L-1 without af fecting fruit size or yield. In the substrate, the plant-derived hydrolysate raised pH and decreased electrical conductivity and nitrate levels, suggesting greater nitrogen use ef ficiency. Potassium was not influenced by the hydrolysate but was af fected by Si doses, particularly at 10 and 20 mg L-1. No significant interactions between the two factors were detected for most evaluated variables. The application of plant-derived protein hydrolysate enhances grape tomato growth and yield, promoting a more stable root-zone environment and greater ef ficiency in nitrate assimilation.